2021
DOI: 10.1108/ijpdlm-05-2020-0163
|View full text |Cite
|
Sign up to set email alerts
|

Exploring blockchain adoption intentions in the supply chain: perspectives from innovation diffusion and institutional theory

Abstract: PurposeDespite blockchain's potential supply chain benefits, few organizations have moved beyond pilot projects. The paper aims to explore blockchain adoption intentions for supply chain applications using two theoretical perspectives: innovation diffusion theory (IDT) and institutional theory (IT).Design/methodology/approachBased on theory, five propositions were developed addressing the intention to adopt blockchain. The propositions were tested using scenario-based experiments with supply chain professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 44 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Consistent with the results of Kl€ ockner et al (2022), this additional variable was also not significant. Both the original hypothesis (H6) and this extension assumed that BT is subject to network effects (Hartley et al, 2022;Schmidt and Wagner, 2019). We thus concluded that -at least at the current level of maturity and diffusion (Durach et al, 2021;Kl€ ockner et al, 2022) -the relevance of network effects in determining the value of BT is limited, as firms mostly implement initiatives involving their current supplier/customer base.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Consistent with the results of Kl€ ockner et al (2022), this additional variable was also not significant. Both the original hypothesis (H6) and this extension assumed that BT is subject to network effects (Hartley et al, 2022;Schmidt and Wagner, 2019). We thus concluded that -at least at the current level of maturity and diffusion (Durach et al, 2021;Kl€ ockner et al, 2022) -the relevance of network effects in determining the value of BT is limited, as firms mostly implement initiatives involving their current supplier/customer base.…”
Section: Discussionmentioning
confidence: 85%
“…The first hypothesis concerns regulation [1], namely those rules and acts with which organizations must comply in terms of transparency, disclosure, traceability, and obligations/restrictions associated with their activities (Hartley et al, 2022;Kalmenovitz, 2023). Regulation has different intensity levels depending on the industry; thus, it is a relevant contingent factor to investigate.…”
Section: Contingent Factors Affecting the Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found out that complexity, cost, competitive pressure, and relative advantage had significant effects on behavioural intention. Innovation diffusion theory (IDT) and institutional theory (IT) too have been utilised to check the intention to use the BT in industries (Hartley et al, 2022 ; Hew et al, 2020 ). Wamba and Queiroz ( 2022 ) applied a set of five theories to empirically study intention to adopt BT.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, scholars can explore questions such as “Why would BT generated transparency and trust lead to better SC relationships, SC integration and SC performance?”. To answer the questions, scholars can explore various theories to address the issues of “causality, explanation, prediction and generalization” from various disciplines such as information sciences and utilise theories such as social exchange theory (Wang et al, 2021b ), institutional theory (Hartley et al, 2022 ), resource based view (Wamba & Queiroz, 2022 ), transaction cost economics (Roeck et al, 2020 ), etc. (Dubey et al, 2022 ).…”
Section: Future Research Agendamentioning
confidence: 99%